Phytoplankton composition and its related environmental conditions in Santubong and Samariang Estuaries, Kuching, Sarawak - Siti Zubaidah, binti Kamarudin (Universiti Malaysia Sarawak (UNIMAS), 2012)
ýA study was carried out to investigate phytoplankton composition in two estuaries of Kuching, Sarawak. Two hundred and two samples of phytoplankton were collected from the estuaries of Samariang and Santubong fortnightly from 2008 to 2011 by using a Van Dorn water sampler and plankton net. Water parameters such as pH, salinity, and temperature were determined in-situ. Selected macronutrients concentration (phosphate, nitrate-nitrogen and silicate) of water samples were analyzed in the laboratory. Phytoplankton enumeration and identification were undertaken by using light and electron microscopy. Ninety five taxa, composed of seventy eight species of diatoms and seventeen species of dinoflagellates were identified from the study area Phytoplankton composition was dominated most by diatom group in both sampling sites but dominated six times in Samariang. The species frequently found predominantly in the water samples of the both sampling sites were Nitzcshia spp., Coscinodiscus spp., Thalassionema spp. and Pleurosigma spp.. The predomination of single genus of phytoplankton at single time resulted in higher cell density and shift in species composition was observed throughout the sampling period. Seasonal occurrence of diatom cell density was recorded from April to August in Santubong and from July to September and April to May and Samariang. Compared to Santubong, dinoflagellates cell density found higher in Samariang. No bloom event of diatom or dinoflagellates was recorded during the sampling period but low Diatom to Dinoflagellates (DD) ratios in some occasion could serve as the window of opportunity for dinoflagellate to bloom. However at this juncture no bloom was observed which could be limit by the change in environmental conditions (pH, salinity, temperature and macronutrients. Statistical analysis with One Way ANOVA showed that higher cell density of diatom and dinoflagellates in both sampling site have significant difference with environmental conditions. However, analysis with Principle Components Analysis (PCA) showed that only pH, phosphate and temperature have positively correlated with cell abundance of diatom and dinoflagellates. In this study, potentially harmful algae such as Pseudo-nitzschia species were frequently detected in the plankton samples. Thus a laboratory experiment to determine the salinity tolerance of Pseudo-nitzschia species was undertaken. In culture experiment, a total of nine strains of four species of Pseudonitzschia showed different, salinity tolerance, in decreasing order of P. pungens > P. brasiliana >P. cuspidata > P. circumpora. Maximal growth rate was greatest in P. pungens (2.21), followed by P. cuspidata (1.57), P. brasiliana (1.52) and P. circumpra (1.01). Morphological abnormality of Pseudo-nitzschia was documented at different salinities and shown to be varied among the species. Irregularity in cell shape was documented in all species while appearance of bulges was observed only in P. pungens and P. cuspidata. Cell abnormality was highest in P. circumpora and lowest in P. cuspidata. In addition, reduction in cell length was observed at all strains but not significant since short duration of experiment applied in this study. Further study using microscosm experiment is important to evaluate the influence of environmental conditions to the changes of phytoplankton compositions especially the abundance and growth of potential harmful species.